Utilization of waste high density polyethylene (HDPE) as a course aggregate replacement with fly ash filler on hot mix asphalt - Norashikin, Abd Razak (2015)
This researched is conducted to investigate the waste HDPE as a coarse aggregate replacement with fly ash as filler on hot mix asphalt The materials used in this studyare using 80/100 grade penetration of bitumen This study focused on three objectives by.usmg ACW14 for determining the optimum bitumen content,;I stiffness modulus andipermanent deformation behaviour using waste HDPE as coarse aggregatereplacemëntbwithflyjash filler on hot mix asphalt. The modified asphalt mixture will be produced fromthe content of waste HDPE in flakes form in range between 2.0%, 4.0%, 60 %, 8.0 %and,10.0%of the asphalt mixture with sieve size 3.35 mm to 1.18 mm. At 5.37 % of optimum bitumen content as followed the hot mix asphalt wearing course 14 (ACW14) was accordance to Public Work Department (PWD) 2008 standard. The samples was tested on Repeated Load Axial Test (RLAT) with 1800 cycles load and axial load applied is 100 kN to determine permanent deformation of modified and unmodified asphalt mixture. The samples; were tested using Indirect Tensile Stiffness Modulus Test (ITSM) to investigate the stiffness modulus modified asphalt mixture at 30 °C. From the results obtain from lab work for the minimum permanent deformation of modified asphalt was 4.0 % of HDPE content. However, the maximum stiffness of HDPE modified asphalt mixture at 4.0,% of .HDPE content. Therefore, HDPE modified asphalt can resist the previôusly mentiänëd road failure, act as environmental friendly and in economic aspect and also found thaVit is suitable to use for road pavement. -